Another economy is possible culture and economy in a time of crisis - Castells, Manuel 1942; Banet-Weiser,Sarah; Hlebik,Sviatlana; Kallis,Giorgos; Pink,Sarah; Seale,Kirsten; Servon,Lisa J.; Swartz,Lana; Varvarousis,Angelos (Malden, MA Polity Press, 2017)
"This book examines the blossoming of innovative new experiments in organizing work and life that emerged in the wake of the financial crisis: cooperatives, barter networks, ethical banking, community currencies, shared time banks, solidarity networks, sharing of goods, non-monetary transactions, etc., experiments that paved the way for the emergence of a sharing economy in all domains of activity oriented toward the satisfaction of human needs"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Financial crisis; Economics